The hippos of Troy : why Homer never talked about a horse - Tiboni, Francesco (Archaeopress Archaeology, 2021)
This title addresses perhaps the most famous episode in Classical mythology: the Wooden Horse of Troy. Through analysis of words, images and wrecks, the author proposes a new interpretation of what Homer actually intended when he spoke of the 'hippos' used by the Greeks to conquer Troy: a particular ship type, used to pay tribute to Levantine kings.